ANALYSIS OF MEAN PLATELET VOLUME, PLATELET DISTRIBUTION WIDTH, AND PLATELET COUNT IN HEMORRHAGIC AND NON-HEMORRHAGIC STROKE - Gita Medita Sunusi; Darwati Muhadi; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Stroke is a sudden and acute focal or global cerebral functional disorder lasting more than 24 hours due to cerebral blood flow impairment. Platelets play an essential role in the pathophysiology of non-hemorrhagic stroke by causing thrombus formation in blood vessels after erosion or rupture of atherosclerotic plaques. Mean platelet volume, PDW and platelet counts are hematological parameters that can be measured on routine blood tests that can describe platelet function and activity and are standard tests carried out in hospitals. The aim of this study was to analyze the differences in MPV, PDW and platelet count between non-hemorrhagic strokes and hemorrhagic strokes. This was a retrospective cross-sectional study conducted in the Dr. Wahidin Sudirohusodo General Hospital of Makassar. A total of 375 Non-Hemorrhagic Stroke (NHS) and 221 Hemorrhagic Stroke (HS) patients were included in this study. Mean platelet volume, PDW and platelet counts were obtained from complete blood count at the time of admission. There was a significant difference in platelet count between NHS and HS patients (p=0.01). Nevertheless, there were no significant differences between MPV and PDW between NHS and HS patients (p=0.19 and p=0.54, respectively). The results of this study indicated that there were significant differences in platelet counts in HS and NHS with increased platelet counts being a risk factor for NHS and a decrease in platelet counts as a risk factor for HS. However, there were no significant differences in the values of MPV and PDW in NHS and HS patients. It is recommended  to study using a better sample selection method so that it can eliminate the occurrence of bias with other diseases, which can also cause a decrease and increase in MPV values, PDW and platelet counts.